AB1164 EDUCATION ON PEDIATRIC MUSCULOSKELETAL ULTRASOUND: A SYSTEMATIC LITERATURE AND EVENTS REVIEW. (June 2019) - Muratore, Valentina; D'agostino, Maria-Antonietta; Naredo, Esperanza; Vojinovic, Jelena; Magni-Manzoni, Silvia
Abstract : Background: Recently some Pediatric musculoskeletal ultrasound (PedMSUS) courses have been held on national and international ground. Nonetheless, content, conduct and format of PedMSUS courses have never been investigated and shared. Objectives: To perform a systematic literature and events review on PedMSUS educational initiatives. Methods: Educational material/events on PedMSUS were extensively searched on websites/networks (PubMed, Cochrane, Embase, ERIC, Medline, CINAHL complete, Google, Yahoo, Ask, Baidu, Bing, Lycos, Duckduckgo). The keywords were: "musculoskeletal", "ultrasound", "sonography", "course", "education", "training", "children", "paediatrics", "pediatrics". Only courses/events, articles and books in English were considered. Descriptive analysis was performed on the documentation retrieved. Results: No articles neither books on educational recommendations for PedMSUS courses were found. A total of 13 PedMSUS courses were identified. Two online courses and three residential ones were not consistent with the purpose and were excluded. Eight courses were finally included for the analysis (Figure 1 ). Seven were endorsed by EULAR and followed the recommendations for the content and conduct of EULAR MSUS courses. No requirements/skills should be fulfilled for registration; only one level of competency was proposed. The courses were residential of 2-3 days and included theorical and practical lessons. Lectures were on MSUS examination techniques, physiological musculoskeletal (MSK) anatomy and basic pathology in pediatric rheumatology. Hands-on scanning of healty models/patients with pediatric rheumatic diseases was generally organized in groups supervised by tutors, and included optimization of the machine settings, identification of pediatric MSK sonoanatomy, correct acquisition of images, and identification of basic pathological findings in children. A competency assessment was performed at the end of only three courses. Legend: NS, not specified; EULAR, European League Against Rheumatism; PReS, Paediatric Rheumatology European Society. *, accommodation, meals and coffee breaks included; #, accommodation excluded; SS, supported by Sponsors; @, dinners excluded. Conclusion: Almost all PedMSUS courses held were under EULAR endorsement. Slightly variable features were found among courses, apart being all at only one level of competency. An international initiative is deserved for identifying shared recommendations on the best suited content, conduct and format of future PedMSUS courses. Disclosure of Interests: Valentina Muratore: None declared, Maria-Antonietta d'Agostino: None declared, Esperanza Naredo Consultant for: Abbvie, Speakers bureau: AbbVie, Roche, Bristol-Myers Squibb, Pfizer, UCB, Lilly, Novartis, Janssen, and Celgene GmbH, Jelena Vojinovic: None declared, Silvia Magni-Manzoni Consultant for: Abbvie, Speakers bureau: Abbvie